Structural, biochemical and computational studies of TRP channel transmembrane domain modularity - Hanson, S (2014)
Transient receptor potential (TRP) channels are expressed throughout the central nervous system and have a unique ability to detect a wide range of stimuli including changes in voltage, temperature, pH, lipid environment, small molecule agonists, and mechanical stress. While it is known that TRP channels contain the same six transmembrane helix (S1-S6), tetrameric architecture as voltage-gated channels, the degree to which functional and structural analogies are relevant remains poorly understood. This thesis describes a multidisciplinary approach toward understanding the structure and function of TRP channel transmembrane domains by focusing on the S1-S4 transmembrane helices of the TRPV1. This focus is inspired by the voltage-sensor domain (VSD) of the S1-S4 helices of voltage-gated channels, for which a range of studies show functional and structural independence. While some TRP channels are voltage-sensitive, their S4 helix does not contain the positive string of amino acids of canonical VSDs. However, the S1-S4 helices are functionally significant as the binding site of small molecule ligands in both TRPV1 and TRPM8 (for capsaicin and menthol, respectively). The question of TRP channel transmembrane domain modularity is addressed in this thesis by expression and purification trials as well as radioligand-binding assays. It is demonstrated that the S1-S4 and S1-S6 helices of TRPV1 can be properly inserted, overexpressed, and show signs of stability upon detergent-extraction from Saccharomyces cerevisiae membranes. However the TRPV1 S1-S4 and S1-S6 helices do not show wildtype (WT)-like binding in [3H]-RTX binding assays. These results indicate that the TRPV1 transmembrane domains are likely structural but not functional domains. The S. cerevisiae expression system remained promising for the overexpression of TRP transmembrane domains as well as the production of functional, though not stable upon detergent-extraction, WT TRPV1. This WT TRPV1 was subsequently found to functionally bind both RTX, used in ligand binding assays, as well as the double-knot toxin (DkTx), targeted to the pore domain (the S5-S6 helices). An effect of DkTx on RTX binding affinity demonstrates an allosteric interaction indicative of a possible tighter packing between the two transmembrane domains than is seen in voltage-gated channels containing the canonical VSD. Computational approaches additionally allowed for the investigation of the intramembrane capsaicin binding site in the TRPV1 S1-S4 helices, crucial to the initial motivations of this study. While the literature locates the capsaicin binding site to the TRPV1 S1-S4 helices, a `binding pocket' has yet to be defined, with regards to the orientation of bound capsaicin and its access route to the site via the bilayer. Using molecular dynamics (MD) simulations the preferred location of capsaicin within the bilayer is defined, as well as the elucidiation of capsaicin flip-flop between bilayer leaflets as a key event prior to TRPV1 binding. A transient binding was also observed between a homology model of the TRPV1 S1-S4 helices and capsaicin, possibly encouraging the idea that the S1-S4 helices still contain a partial binding site, though of too low affinity to be observed in the binding experiments performed here.